The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/su15032802
|View full text |Cite
|
Sign up to set email alerts
|

A State-of-the-Art Review and Numerical Study of Reinforced Expansive Soil with Granular Anchor Piles and Helical Piles

Abstract: Expansive soils exist in many countries worldwide, and their characteristics make them exceedingly difficult to engineer. Due to its significant swelling and shrinkage characteristics, expansive soil defies many of the stabilization solutions available to engineers. Differential heave or settlement occurs when expansive soil swells or shrinks, causing severe damage to foundations, buildings, roadways, and retaining structures. In such soils, it is necessary to construct a foundation that avoids the adverse eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…The present study employs the same methodology and materials properties as Alnmr et al [69]. For further details, please refer to [69].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study employs the same methodology and materials properties as Alnmr et al [69]. For further details, please refer to [69].…”
Section: Methodsmentioning
confidence: 99%
“…The present study employs the same methodology and materials properties as Alnmr et al [69]. For further details, please refer to [69]. Figure 8 illustrates a cross-sectional view of unreinforced and reinforced soil with helical and granular anchor piles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary application of the soil-water characteristic curve (SWCC) is to evaluate the performance of unsaturated soil properties for a range of geotechnical engineering applications [1]. One common application of SWCCs in geotechnical engineering is to assess the hydraulic properties necessary to simulate water flow through unsaturated soils [2][3][4][5][6]. The SWCC shape reflects the soil's water retention capacity and porosity characteristics, enabling the estimation of various engineering properties such as hydraulic conductivity, shear strength, and diffusion coefficient [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Nelson and Miller [7] assert that expansive soils may result in greater financial losses than earthquakes or floods. In addressing this challenge, the behavior of expansive soils has been studied in numerous studies by adding different materials to improve their characteristics [8][9][10][11][12][13][14][15]. Although these studies have shown that soil characteristics can be improved via the addition of materials, many unresolved questions remain.…”
Section: Introductionmentioning
confidence: 99%